Glucobrassicin hydrolysis by human gut bacteria and putative glycosyl hydrolases involved in the process - Albaser, Abdulhadi Ali; Rossiter, John Trevor; Luang-In, Vijitra (Food Agricultural Sciences and Technology, 2023)
Hydrolysis of glucobrassicin by plant or bacterial myrosinase produces multiple indoles predominantly indole-3-carbinol (I3C) and 3,3’-diindolylmethane (DIM), which show promise in clinical trials as effective cancer chemopreventive agents. This work aimed to study the capacity of two human gut bacteria; Escherichia coli VL8 and Enterococcus casseliflavus CP1 to hydrolyze glucobrassicin from yellow mustard (Sinapis alba) seeds. Myrosinase-positive bacteria from enrichment culture were cultured in media containing 0.1 mM glucobrassicin for 16 h. The HPLC results showed that E. casseliflavus CP1 was able to degrade glucobrassicin by 73% at 16 h, whilst E. coli VL8 gave 47% degradation. The putative glycosyl hydrolase (GH) enzymes from E. casseliflavus CP1 involved in the hydrolysis were predicted based on the UniProt database, cloned, inserted into the pET28b(+) vector and expressed in E. coli BL21(DE3) as recombinant enzymes using IPTG inducer. All the tested recombinant GH enzymes did not exhibit myrosinase activity towards glucosinolate substrate; however, some displayed GH and/or β-glucosidase activity towards various sugars using GOD-PERID and β-glucosidase assays. These enzymes may be inactive in the pH buffers used or activity only occurs in intact cells where the integrity of transport/phosphorylation system is intact. In spite of some caveats in this work, the findings would still be useful to better understand glucosinolate metabolism by human gut bacteria which is liked with chemopreventive benefits.